Well-being and help-seeking: an exploratory study among final-year medical students - Leão,Paula Bertozzi de Oliveira e Sousa (2011)
OBJECTIVE: Doubts, competitiveness and preparation for the residency examination increase stress and insecurity at the end of medical course. Well-being is very important at this point, but it is known that medical students are reluctant to seek help, particularly for emotional problems. This study investigated the relationship among well-being, perceived needs and help-seeking in final-year students. METHODS: Well-being was assessed using Beck's Inventories of Anxiety (BAI) and Depression (BDI) and the WHOQOL-brief (quality of life). A questionnaire was used to assess perceived needs and medical school support resources. RESULTS: The students reported good quality of life (68%) but presented anxiety (27%), depression (20%) and impaired social functioning. Fifty-one percent of the students acknowledged academic needs and 25% psychological needs. Only a portion of the students with anxiety and depression or bad quality of life used the institutional support. Female gender, perceived psychological needs and anxiety symptoms were associated to the use of the Mental Health Service. Satisfaction with mentoring relationships and positive changes were associated to Mentoring attendance. CONCLUSION: There are different factors involved in help-seeking and identifying specificities in the use of institutional support resources can help to develop strategies to sensitize students about help-seeking during the medical course